Effect of Supplier Relationship Management on Humanitarian Supply Chain Performance at the World Food Programme in Somalia - Rucha, Kingsford M.; Abdallah, Amina Nassor (European Scientific Journal, ESJ, 2017)
The study sought to unfold the relationship between Supplier Relationship Management on supply chain in humanitarian organizations which is often difficult because of the multi-groups involved (military, government, Non-governmental Organizations). In humanitarian organizations the â€œcustomerâ€ is the donor or supplier of goods. The study was conducted at the World Food Programme (WFP) which started operating in Somalia in 1967 and focusing on rural agricultural development and school feeding projects. At the onset of WFP operations, the conflict escalated and the humanitarian needs expanded as well. Today the WFP Somalia goal is to address basic food needs, strengthen coping mechanisms and support the efforts to achieve food security of vulnerable Somalis. The organization has its regional office in charge of operations and supply chain in Nairobi as well as the Somalia liaison office. There are rare studies focusing on supply chain relationship among humanitarian organizations particularly on the challenges of getting supplies on time due financial and other supply chain constraints. This is the gap this study sought to address. In order to achieve the objectives, the population of the study was the WFP employees (senior and the supply chain staff) in both the regional and the liaison office and the WFP food suppliers based in Nairobi. The sample comprised of 87 WFP employees and 7 personnel from the WFP food supplier family. Data was collected from 63 respondents who filled and returned the questionnaires representing a response rate rate of 72%. Multiple regression analysis was used to analyse the data collected in order to meet the objectives of the study. The results revealed that WFP continuously trains employees from the supply chain department and has mechanisms for ensuring suppliers conform to quality standards. It was also found that ICT is used in the execution and management of purchase orders. On WFP humanitarian supply chain performance, results indicated that WFP Somalia delivers defect free food supplies to beneficiaries by working closely with the internal staff and the logistics operators. The study recommends that WFPâ€™s management should begin rewarding suppliers who share information for effective supply chain management. The organization should not only have multiple supply tiers but should also be well vast with each tiers risk profile to enable the organization mitigate any unforeseen events that may affect delivery of supplies especially during emergencies.